PENGARUH DIMENSI KUALITAS PELAYANAN ACCOUNT REPRESENTATIVE DAN TINGKAT PENDIDIKAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi pada KPP Pratama Makassar Barat) - Indrayani, Indrayani (Economos : Jurnal Ekonomi dan Bisnis, 2020)
This study aims to analyze the effect of the account representative service quality dimension and taxpayer education level on individual taxpayer compliance. The number of taxpayers is increasing from year to year, but it is not balanced with taxpayer compliance in paying taxes. This compliance problem becomes an obstacle in maximizing tax revenue. This study examines the level of compliance of individual taxpayers registered in area of the KPP Pratama Makassar Barat by using several independent variables, namely direct evidence, reliability, responsiveness, assurance, and empathy as dimensions of Account Representatives service quality and taxpayers education level. The data used in this study are primary data obtained from the research location, namely through the distribution of questionnaires (a list of questions to respondents). The sample consists of 100 respondents who are individual taxpayers and secondary data obtained from KPP Pratama Makassar Barat which is closely related. The data was tested using multiple linear regression analysis. The data were tested using SPSS 20. The researcher also test the validity and reliability tests for the questionnaire. The classical assumption test used was the multicollinearity test, normality test, and heteroscedasticity test. For hypothesis testing, researcher using the coefficient of determination (R2), simultaneous test (F-test), and partial test (t-test). Based on the results of the analysis conducted, it is concluded that direct evidence, reliability, responsiveness, and assurance have a positive effect but insignificant, while empathy has a positive effect and significant, while education level has a negative effect and insignificant on individual taxpayer compliance at KPP Pratama Makassar Barat.